2022
DOI: 10.1021/acs.joc.2c02106
|View full text |Cite
|
Sign up to set email alerts
|

Engineered, Scalable Production of Optically Pure l-Phenylalanines Using Phenylalanine Ammonia-Lyase from Arabidopsis thaliana

Abstract: An efficient preparative-scale synthetic procedure of l-phenylalanine derivatives has been developed using mutant variants of phenylalanine ammonia-lyase from Arabidopsis thaliana (AtPAL). After rigorous reaction engineering, the AtPAL-catalyzed hydroamination reaction of cinnamic acids provided several unnatural amino acids of high synthetic value, such as (S)-m- and (S)-p-methoxyphenylalanine; (S)-o- and (S)-m-methylphenylalanine; and (S)-o- and (S)-p-bromophenylalanine at preparative scale, significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Since our previous results revealed a high catalytic efficiency of La AAL within the ammonia addition reaction route, [8] we shifted our focus towards the applicability of La AAL within this asymmetric synthetic route of high industrial interest. While prior studies revealed that concentrated (3–6 M) solutions of ammonium–hydroxide [3b,c] and ammonium–carbamate [4c,13] are optimal ammonia sources for the PAL–catalyzed ammonia additions, the effect of pH was less explored and reported for this reverse PAL–reaction. Testing 4 M NH 4 OH solutions of different pH values ranging from 9.0 to 11.5 (adjusted with CO 2 ), the highest enzyme activity was observed at pH 9.0 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Since our previous results revealed a high catalytic efficiency of La AAL within the ammonia addition reaction route, [8] we shifted our focus towards the applicability of La AAL within this asymmetric synthetic route of high industrial interest. While prior studies revealed that concentrated (3–6 M) solutions of ammonium–hydroxide [3b,c] and ammonium–carbamate [4c,13] are optimal ammonia sources for the PAL–catalyzed ammonia additions, the effect of pH was less explored and reported for this reverse PAL–reaction. Testing 4 M NH 4 OH solutions of different pH values ranging from 9.0 to 11.5 (adjusted with CO 2 ), the highest enzyme activity was observed at pH 9.0 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…This approach involved the identification of key active side residues L90, F93 and L205 responsible for the stereoselectivity of hydroamination, followed by the creation of a targeted library of variants. Although the position corresponding to L205 in Pb PAL (L256 in Pc PAL, L257 in At PAL2, L266 in PAL from Rhodosporidium toruloides ( Rt PAL), respectively) was previously subjected to mutagenesis in eukaryotic PALs to improve the yields of hydroamination, [11,20] it has not been used to improve the enantioselectivity of these reactions. Likewise, in a study uncovering Av PAL variants with altered enantioselectivity for 4‐nitrocinnamic acid hydroamination conducted by Turner and co‐workers, although 48 residues near the substrate binding site were subjected to NNK site‐saturation mutagenesis, the corresponding L219 residue (equivalent to L205 in Pb PAL) was omitted [30] .…”
Section: Figurementioning
confidence: 99%
“…Enzyme engineering efforts to enhance the practical applications of PALs focused on increasing substrate versatility for synthesizing various non-natural ortho-, meta-, and para-substituted L-phenylalanines, utilizing PALs from various sources, including Petroselinum crispum (PcPAL) [9][10][11][12][13][14][15] , Anabaena variabilis (AvPAL), [8,[16][17][18] Arabidopsis thaliana (AtPAL), [19,20] and Planctomyces brasiliensis (PbPAL) [21] (Figure 1B). While engineered PALs efficiently catalyze hydroamination reactions on various substituted aromatic arylacrylic acids, they still clearly exhibit a narrow specificity for this substrate class.…”
mentioning
confidence: 99%
“…Since product inhibition has been observed for Pc PAL, PALs from different organisms, such as Arabidopsis thaliana ( At PAL) or Rhodosporidium toruloides ( Rt PAL) have been engineered for improved catalytic efficiency [98,99] . Gram‐scale synthesis of several L‐phenylalanine derivatives was lately achieved by a whole‐cell biocatalyst comprising engineered At PAL [100] . Another emerging biocatalyst is EDDS lyase, which catalyzes the reversible degradation of ( S , S)‐ EDDS via two sequential deamination steps [28] .…”
Section: C−o and C−n Bond‐forming Enzymes—an Overviewmentioning
confidence: 99%
“…[98,99] Gram-scale synthesis of several L-phenylalanine derivatives was lately achieved by a whole-cell biocatalyst comprising engineered AtPAL. [100] Another emerging biocatalyst is EDDS lyase, which catalyzes the reversible degradation of (S,S)-EDDS via two sequential deamination steps. [28] Poelarends and coworkers showed the potential of EDDS-lyase, as well as 3methylaspartate ammonia lyase, as biocatalyst for the asymmetric synthesis of various aspartic acid derivatives, showcasing its broad amine scope.…”
Section: Cà N Bond-forming Enzymesmentioning
confidence: 99%